2011
DOI: 10.1080/11250003.2010.490566
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationship betweenCallosciurus canicepsandC. inornatus(Rodentia, Sciuridae): Implications for zoogeographical isolation by the Mekong River

Abstract: To test the riverine barrier hypothesis in small arboreal mammals, we examined phylogenetic relationship between two Callosciurus squirrel species (C. caniceps and C. inornatus) geographically isolated in the northeastern part of the Indochina Peninsula by the Mekong River. We did this by comparing complete mitochondrial DNA cytochrome b gene sequences of these two squirrels and five other Callosciurus species: C. erythraeus, C. finlaysonii, C. nigrovittatus, C. notatus, and C. prevostii. Phylogenetic trees sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 22 publications
(23 reference statements)
1
5
0
Order By: Relevance
“…This finding is consistent with the landscape of S.E. Asia, and in particular the marine barriers between the different land masses, which almost certainly affect the dispersal and genetic connectivity for small mammals such as Callosciurus species (Oshida et al 2011;Brunke et al 2019). In addition, Callosciurus notatus has also been reported as a genetically diverse species subdivided into several subspecies around Southeast Asia (Chah 2007;Sari et al 2020).…”
supporting
confidence: 69%
See 1 more Smart Citation
“…This finding is consistent with the landscape of S.E. Asia, and in particular the marine barriers between the different land masses, which almost certainly affect the dispersal and genetic connectivity for small mammals such as Callosciurus species (Oshida et al 2011;Brunke et al 2019). In addition, Callosciurus notatus has also been reported as a genetically diverse species subdivided into several subspecies around Southeast Asia (Chah 2007;Sari et al 2020).…”
supporting
confidence: 69%
“…Asia, and in particular the marine barriers between the different land masses, which almost certainly affect the dispersal and genetic connectivity for small mammals such as Callosciurus species (Oshida et al. 2011 ; Brunke et al. 2019 ).…”
mentioning
confidence: 99%
“…Recent studies in other regions of the world have demonstrated the importance of rivers as barriers to gene flow (Oshida et al 2011;Rocha et al 2011;Ćosić et al 2013), and verified the strong effect of anthropogenically modified landscapes on dispersal capabilities and genetic connectivity in small mammals (Gerlach and Musolf 2000;Trizio et al 2005;Stephens et al 2013;Bani et al 2017). But most studies investigating the effect of geographic barriers on dispersal and genetic structure have mainly focused on a single species (Patton et al 1994;Colombi et al 2010;Nicolas et al 2011;Ćosić et al 2013;Russo et al 2016), or few species from the same genus (Kennis et al 2011;Oshida et al 2011;Rocha et al 2014). This study is to our knowledge the first investigating the influence of different landscape features on migration and population connectivity in a comprehensive community of Bornean small mammals.…”
Section: Introductionmentioning
confidence: 91%
“…It was suggested that the Mekong River has acted as a zoogeographical barrier at least in small mammals during the Pliocene and Pleistocene [ 27 ]. The cases of Callosciurus squirrels [ 30 , 31 , 32 ], genetic differentiation or speciation has been demonstrated between both sides of this river. In northern treeshrew of North Vietnam population, however, the t -test using raw data demonstrated that the total number of the siginificantly different measurements were few between Y and 2, Y and 3, and Y and 4 in both sexes and Y and 7 in male ( Table 7 ).…”
Section: Discussionmentioning
confidence: 99%